Publicación web de trabajos de investigación usando Lenguaje de Marcado Extensible - Diosa, Henry Alberto (Ingeniería, 2000)
XML, the eXtensible Markup Language allows to separate the structural abstraction of a group of documents of their content and presentation; this means that three layers or levels of a document can be determined: · Their structural abstraction or Document Type Definition(DTD). · Their content based on having labeled or XML document. · Their defined presentation through Style Sheets. This modulate vision of a document allows to outline a solution to show in the WEB the information of degree projects and investigations according to the documentation standards and scope of contents defined by an institution; in this article,for clarity and easiness of understanding, a very basic example is developed, diffusing of records investigation summary by means of a WEB site that give to know to the external and internal community of the university around the works that one comes developing or they have ended, developed by students or specific work groups, with the connotation of being a simple and relatively easy procedure of implanting.